IMPLEMENTASI SUSTAINABLE TOURISM DI KAWASAN WISATA ALAM BUKIT SIKUNIR, DIENG - Shabrina, Yusfi; Octavanny, Vitha; Nasir, Syeda Zainab; Ferentya, Marsha Desty (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
Abstract Sustainable tourism is a concept that is increasingly gaining attention amidst the increase in tourism activities that have an impact on the environment and local communities. The focus of this research is to analyze the economic, social, and environmental impacts of tourism activities in Sikunir Hill, as well as how local communities are involved in sustainable tourism management. By using qualitative methods that are analytical and descriptive through data collection techniques by conducting observations, interviews, documentation studies and analyzing literature reviews related to sustainable tourism. The results showed that tourism in Sikunir Hill provides a significant economic contribution to the local community through increased income from the tourism sector. However, negative impacts on the environment, such as ecosystem damage and increased waste volume, are also a serious concern. In addition, education and environmental awareness for tourists also need to be improved to minimize negative impacts on nature. Thus, tourism in Sikunir Hill can continue to grow without compromising environmental sustainability and the welfare of the local community. Keywords: Sustainable Tourism; Natural Attraction; Sikunir Hill AbstraksPariwisata berkelanjutan merupakan konsep yang semakin mendapatkan perhatian di tengah peningkatan aktivitas wisata yang berdampak pada lingkungan dan masyarakat setempat. Fokus penelitian ini adalah untuk menganalisis dampak ekonomi, sosial, dan lingkungan dari aktivitas wisata di Bukit Sikunir, serta bagaimana keterlibatan masyarakat lokal dalam pengelolaan pariwisata yang berkelanjutan. Dengan menggunakan metode kualitatif yang bersifat analisis dan deskriptif melalui teknik pengumpulan data dengan melakukan observasi, wawancara, studi dokumentasi dan analisis tinjauan literatur terkait pariwisata berkelanjtuan. Adapun hasil penelitian menunjukkan bahwa pariwisata di Bukit Sikunir memberikan kontribusi ekonomi yang signifikan bagi masyarakat setempat melalui peningkatan pendapatan dari sektor pariwisata. Namun, dampak negatif terhadap lingkungan, seperti kerusakan ekosistem dan peningkatan volume sampah, juga menjadi perhatian serius. Selain itu, edukasi dan kesadaran lingkungan bagi wisatawan juga perlu ditingkatkan untuk meminimalkan dampak negatif terhadap alam. Dengan demikian, pariwisata di Bukit Sikunir dapat terus berkembang tanpa mengorbankan kelestarian lingkungan dan kesejahteraan masyarakat setempat.Kata Kunci: Sustainable Tourism; Kawasan Wisata Alam; Bukit Sikunir